2014
DOI: 10.1088/0031-8949/89/9/095210
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order rogue wave solutions of the Kundu–Eckhaus equation

Abstract: In this paper, we investigate higher-order rogue wave solutions of the Kundu-Eckhaus equation, which contains quintic nonlinearity and the Raman effect in nonlinear optics. By means of a gauge transformation, the Kundu-Eckhaus equation is converted to an extended nonlinear Schrödinger equation. We derive the Lax pair, the generalized Darboux transformation, and the Nth-order rogue wave solution for the extended nonlinear Schrödinger equation. Then, by using the gauge transformation between the two equations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 64 publications
3
75
0
Order By: Relevance
“…This solution and some other analytical solutions are given in [8][9][10]. This first order rational rogue wave is basically a skewed Peregrine soliton of the NLSE.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…This solution and some other analytical solutions are given in [8][9][10]. This first order rational rogue wave is basically a skewed Peregrine soliton of the NLSE.…”
Section: Introductionmentioning
confidence: 85%
“…where ψ is complex amplitude, x, t are the spatial and temporal variables and i is the imaginary number [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2(b). The analogous phenomena produced by the higher-order effects have been comprehensively studied for rogue waves in the Hirota equation [24], Sasa-Satsuma equation [25] and Kundu-Eckhaus equation [36,39], while for the coupled system without any higher-order terms they have been rarely reported.…”
Section: Rogue Wavementioning
confidence: 99%
“…The purpose of this paper is mainly concentrated on two aspects: (1) we construct an Nth-order rational solution in a compact determinant representation by taking advantage of the generalized DT approach [33][34][35][36]; (2) With the aid of the analytical rational solution and modulation instability (MI), dynamics of the optical rogue waves, as well as the stationary and nonstationary W-shaped solitons from first to third order are presented. In particular, it is importantly found that, the nonstationary W-shaped solitons can only exist in the multiple SIT system, while for the single system they are impossible to appear.…”
Section: Introductionmentioning
confidence: 99%